2006
DOI: 10.1271/bbb.70.639
|View full text |Cite
|
Sign up to set email alerts
|

Expression Analysis of Genes for Callose Synthases and Rho-Type Small GTP-Binding Proteins That Are Related to Callose Synthesis in Rice Anther

Abstract: The most chilling-sensitive stage of rice has been found to be at the onset of microspore release. The microsporocytes produce a wall of callose between the primary cell wall and the plasma membrane, and it has been shown that precise regulation of callose synthesis and degradation in anther is essential for fertile pollen formation. In this study, genes for 10 callose synthases in the rice genome were fully annotated and phylogenetically analyzed. Expression analysis of these genes showed that OsGSL5, an orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 23 publications
(25 reference statements)
1
27
0
Order By: Relevance
“…Aniline blue staining showed the irregular stacking of callose on the mutant meiocytes (Figure S2). We monitored the expression levels of OsGSL5 (putative glucan synthase gene, AP003454 ), which encodes an anther‐specific callose synthase (Yamaguchi et al. , 2006), and Osg1 (glucanase, AB070742 ), which is required for callose degradation (Wan et al.…”
Section: Resultsmentioning
confidence: 99%
“…Aniline blue staining showed the irregular stacking of callose on the mutant meiocytes (Figure S2). We monitored the expression levels of OsGSL5 (putative glucan synthase gene, AP003454 ), which encodes an anther‐specific callose synthase (Yamaguchi et al. , 2006), and Osg1 (glucanase, AB070742 ), which is required for callose degradation (Wan et al.…”
Section: Resultsmentioning
confidence: 99%
“…It is located between the cellulose cell wall and plasma membrane, playing a key role in the process of fertile pollen formation (Worrall et al 1992). Abnormal regulation of callose synthesis and dissolution may affect proper pollen wall formation (Chen et al 2007;Dong et al 2005;Worrall et al 1992;Yamaguchi et al 2006). In the present research, four microspores without a callose wall were observed held together in a tetrad-like structure in the anthers of the male sterile plant from 01GAB.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 10 GSLs in rice, the expression of OsGSL5 was dramatically downregulated by cool treatment, it indicated that cool conditions affected GSL activity (especially GSL5) during male reproductive development. 41 Phytosphingosine, an inhibitor of yeast GSLs in vivo, was shown to be located at the endoplasmic reticulum. 42 In Neurospora crassa and higher plants, the FKS domain of GSLs binds directly to UDP-glucose.…”
Section: Callose Biosynthesis During Male Reproductive Development Inmentioning
confidence: 99%